2013
DOI: 10.26719/2013.19.supp3.s6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status of type 2 diabetic patients compared with healthy subjects in the Islamic Republic of Iran

Abstract: An inverse relationship has been shown between vitamin D deficiency and type 2 diabetes mellitus (DM). In this cross-sectional study in Tehran, Islamic Republic of Iran, a country with a high prevalence of vitamin D deficiency, we determined the prevalence of vitamin D deficiency among 90 type 2 DM patients and 90 healthy subjects. Based on serum levels of 25-hydroxyvitamin D, the rates of deficiency (< 50 nmol/L) and insufficiency (50-75 nmol/L) were 59.0% and 27.0% respectively in patients with type 2 DM, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Additionally, genetic changes in vitamin D receptors are associated with an increased risk of DM. A recent cross-sectional study conducted in Tehran, Iran detected a higher prevalence of vitamin D deficiency in patients with than without type 2 DM (37).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, genetic changes in vitamin D receptors are associated with an increased risk of DM. A recent cross-sectional study conducted in Tehran, Iran detected a higher prevalence of vitamin D deficiency in patients with than without type 2 DM (37).…”
Section: Discussionmentioning
confidence: 97%
“…They showed that the prevalence of vitamin D deficiency (< 50 nmol/L) was significantly higher in the case (58.9%) than in the control groups (47%). Mean of age, BMI and vitamin D3 were lower in the case group, but not significantly [6].…”
Section: Discussionmentioning
confidence: 67%
“…An upward trend in the incidence rate among the Iranian population suggests 9.2 million diabetes patients by 2030 [2][3][4][5]. Type 2 diabetes (T2D) has high morbidity and mortality rates (fifth leading cause of death in the Iranian population) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The present results revealed that the number of cases having vitamin D deficiency and insufficiency were significantly higher than that of controls. Vitamin D deficiency and insufficiency were found to be prevalent among type 2 diabetic patients [34][35][36]. When compared with controls, cases showed significant decrease in the mean level of serum vitamin D. This means that deficiency in vitamin D levels are linked to type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%